Prostatism: how useful is routine imaging of the urinary tract?. Issue 6627 (2nd April 1988) - de Lacey, Gerald; Johnson, Stephen; Mee, David
Abstract : The clinical effects of routinely imaging the renal tract (by intravenous urography and ultrasonography) were evaluated prospectively in 128 consecutive patients with prostatism. Patients with haematuria, previous renal disease, or infection were excluded. Urologists completed a standard questionnaire in the patient's notes stating the diagnosis and the intended management. The patient then had intravenous urography and abdominal ultrasonography, urine was analysed, and plasma urea and serum creatinine concentrations and acid phosphatase activity were determined. From six months to a year later the eventual management was compared with the intended management to see the effect of these routine investigations on the outcome. For four out of 28 patients whose management was intended to be conservative the decision was changed; for only three of them was this because of the results of urography, ultrasonography, and biochemical determinations. For 31 patients the management was to be decided by cystoscopic findings, and for none of these was the final decision altered by the results from the investigations after the initial consultation. Similarly for five patients who were assessed urodynamically the final management was not changed by the results of these investigations. The planned management was changed in three of the remaining 64 patients but not because of the results of the initial investigations. Thus no indication was found for either routine urography or ultrasonography, but the total abandonment of imaging of the renal tract would be unwise. Patients scheduled for conservative management (about a quarter of the patients in this study) should have ultrasonography to detect unsuspected hydronephrosis, but in all other patients urography or ultrasonography, or both, is an unhelpful ritual. Moreover, urography is becoming more expensive, and has a recognised (albeit small) mortality.